A MODERNIDADE E A PROBLEMÁTICA DA PRODUÇÃO, DO CONSUMO, DA GERAÇÃO E DESTINAÇÃO DE RESÍDUOS - Vieira, Elias Antônio (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2011)
This paper is adapted from a dissertation topic Master defended by the author in 2002.Was motivated by the concern with the fact that the sources do not always associate the problemof waste to Mode of Production and Consumption Capitalist – MPCC of Modernity. The centralhypothesis of this study is that knowledge of the characteristics and context of this period cancontribute to the prevention or reduction of potential negative environmental impacts of thesematerials. The key points of the literature review that guided the work covered the definition andhistory of the period mentioned, its evolution and relation to waste management issues.Regarding the survey results showed that the authors had taken into account the various formsand degrees to which the MPCC not only articulates and organizes geographic space, but also therapid pace that gives the production and consumption and therefore the continued and increasinggeneration of waste.